Design of synchronous salient pole machines - Yurieva, O.; Shilkova, L. (National Technical University "Kharkiv Polytechnic Institute", 2024)
From all electrical machines, the largest and smallest is indeed the synchronous machine. The largest electrical machine is a generator of a thermal power plant with a capacity of 1.75 GW, while the smallest is a computer cooler motor with a power of 4 W. Such a range of powers and wide application has led to the emergence of a number of individual types of synchronous machines: turbo generators, hydro generators, diesel generators, synchronous motors, synchronous compensators, stepper motors, hysteresis motors, reactive synchronous motors. In high-speed synchronous machines, the rotors are of nonsalient pole design, while at relatively low rotational frequencies, they are of salient pole design. Salient pole design is used in the manufacturing of synchronous generators, synchronous motors, synchronous compensators. Synchronous generators are used in mobile and stationary electrical stations and are driven by internal combustion engines or hydraulic turbines. Synchronous motors are used in installations that do not require speed regulation or require maintaining a constant rotational frequency under variable load. Synchronous motors with an excitation winding have a unique property of generating reactive power in electrical installations to increase the network power factor. Synchronous compensators are used for the same purpose and are installed in electrical network substations.
Keywords: educational and methodological manual; technical specifications; stator design; rotor design; magnetic calculation; field winding design; thermal calculation